The spotted dog [compact disc, unabridged] - Greenwood, Kerry (Greenwood, Kerry. Corinna Chapman mystery., 2018)
When a distraught Scottish veteran from Afghanistan is knocked unconscious, waking up to find his beloved ex-service dog missing, Corinna and her lover, Daniel, find themselves inextricably drawn into the machinations of a notorious underworld gang of drug runners. Corinna and Daniel need to pull together all the strings to find the connections between their wandering Scottish veteran, his kidnapped dog, a student dramatic society that's moved into Corinna's building, burglaries, and the threatening notes that begin to mysteriously appear in Corinna's apartment. Between her forays into danger, there is still time in Corinna's life for tender encounters as the delicious aromas of newly baked breads, muffins and treats waft out of Corinna's bakery, Earthly Delights.